Analysis of the effectiveness of modern information and communication technologies on maize marketing efficiency in Malawi markets - Chowa, Sarah E. Tione (International Food Policy Research Institute, 2014)
In 2004, the government of Malawi introduced the Malawi Agriculture Commodity Exchange under the Initiative for Devel-opment and Equity in African Agriculture program, which promoted modern information and communication technologies (ICT) to improve access to agricultural market information for both suppliers and buyers of market produce. Using co-integration error correction models, this study assesses the effectiveness of modern ICT-based market interventions in improving maize market efficiency in Malawi. A Threshold Autoregressive Error Correction model was used to assess price transmission speed. Comparisons were made of the speed of price transmission in the periods before and after the intro-duction of ICT technologies by the Malawi Agriculture Commodity Exchange - Initiative for Development and Equity in African Agriculture in 2004. The spatial integration results show that maize markets in Malawi were better integrated fol-lowing the introduction of ICT-based market interventions.